Design and development of a remote monitoring system for fuel cells - Komweru, Laetitia (My University, 2006)
This dissertation presents the design and development of a remote monitoring system (RMS) for polymer electrolyte membrane fuel cells (PEMFC) to facilitate their efficient operation. The RMS consists of a data acquisition system built around the PIC 16F874 microcontroller that communicates with a personal computer (PC) by use of the RS232 serial communication standard, using a simple wired connection between the two. The design also consists of a human machine interface (HMI) developed in Visual Basic 6.0 to provide a platform for display of the monitored parameters in real time. The first objective was to establish performance variables and past studies on PEM fuel cells revealed that variables that affect the system's performance include: fuel and oxidant input pressure and mass flow rates as well as operation temperature and stack hydration. The next objective was to design and develop a data acquisition system (DAS) that could accurately measure the performance variables and convey the data to a PC. This consisted of sensors whose outputs were input into two microcontrollers that were programmed to process the data received and transfer it to the PC. A HMI was developed that provided graphical display of the data as well as options for storage and reviewing the data. The developed system was then tested on a 150Watt PEM fuel cell stack and the data acquisition system was found to reliably capture the fuel cell variables. The HMI provided a real-time display of the data, with alarms indicating when set minimums were exceeded and all data acquired was saved as a Microsoft Excel file. Some recommendations for improved system performance are suggested.
M. Tech. (Engineering, Electrical, Department Applied Electronics and Electronic Communication, Faculty of Engineering and Technology) -- Vaal University of Technology
Keywords: Remote monitoring system; Polymer electrolyte membrane fuel cells; Fuel cells; 621.312429; Fuel cells